2018
DOI: 10.1007/s00590-018-2212-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of edoxaban for the patients with postoperative anemia after total hip arthroplasty

Abstract: The frequency of postoperative anemia was increased in patients treated with edoxaban, compared to fondaparinux, after THA. Edoxaban thromboprophylaxis might, therefore, require more careful monitoring to prevent postoperative anemia. Additionally, particular prolongation of PT and PT-INR induced by edoxaban treatment might predict postoperative anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Furthermore, the difference in Hb between groups was 0.1–0.6 g/dL, which is much less than a clinically important difference in Hb of 1.0–2.0 g/dL [27,28]. This finding is consistent with some previous reports, which showed that edoxaban administration after THA resulted in more anemia [7,8]. However, another study showed that prophylactic edoxaban administration after TKA did not increase the incidence of major or clinically relevant non-major bleeding [29].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the difference in Hb between groups was 0.1–0.6 g/dL, which is much less than a clinically important difference in Hb of 1.0–2.0 g/dL [27,28]. This finding is consistent with some previous reports, which showed that edoxaban administration after THA resulted in more anemia [7,8]. However, another study showed that prophylactic edoxaban administration after TKA did not increase the incidence of major or clinically relevant non-major bleeding [29].…”
Section: Discussionsupporting
confidence: 90%
“…Administration of 60 mg/day edoxaban resulted in a larger hemoglobin (Hb) drop than 10 mg/day apixaban administration for treatment of DVT after TKA or THA [7]. Prophylactic administration of 30 mg edoxaban after THA is associated with more anemia than administration of 2.5 mg fondaparinux [8]. However, Fuji et al reported that oral edoxaban 30 mg once daily was superior to subcutaneous enoxaparin 2000 IU twice daily for preventing VTE following THA without increasing the risk for major or clinically relevant non-major bleeding [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 , 11 ] Next, the risk factors for anemia in patients who underwent Edx treatment after surgery were retrospectively investigated in a case−control study as the secondary analysis of 2 previous studies. [ 5 , 6 ] Finally, the association of the detected risk factors for anemia with the hemoglobin (Hgb) levels, coagulation parameters, and transfusion during Edx treatment after surgery was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…However, Edx treatment increased the frequency of anemia after TKA/THA compared with fondaparinux, the primary conventional anticoagulant, at only a single center. [ 5 , 6 ] Therefore, the risk of anemia with Edx treatment remains elusive. Additionally, no information is available regarding the risk factors for anemia before initiating Edx treatment.…”
Section: Introductionmentioning
confidence: 99%